(Geo)Politics of Universal Periodic Review: Why States Issue and Accept Human Rights Recommendations?. Issue 4 (18th August 2021) - Burger, Anze; Kovac, Igor; Tkalec, Stasa
Abstract: The research identifies geographic proximity as the crucial driving force behind state behavior in the Universal Periodic Review (UPR). Looking at both stages of the UPR mechanism, we pose two questions: what best explains states issuing human rights recommendations and what best explains states accepting those recommendations? Our model controls for a variety of alternative explanations—state capacity, international structure, and international institutions. The results show that the closer the states are, the more likely it is that they will issue each other recommendations; however, the closer the states are, the less likely it is that they will accept recommendations from one another. We also find an important caveat: the logic of issuance and acceptance of recommendations is reversed when it comes to neighboring states. The latter speaks against general international relations literature, where sharing a border and geographic proximity are both associated with increasing the likelihood of conflict.